The Relatedness of Community Perception with The Actions in Forest Pest Management - Haneda, Noor Farikhah; Yulius Hero,; Derry Ferdani Rustanzi, (Journal of Sylva Indonesiana, 2021)
Pest attack on the forest can have an impact on the productivity and quality of existing stands (such as reducing average plant growth, decreasing seed germination power, and appearance of forest aesthetics). This study aims to identify the types of pest management and analyze the relationship between perception and community actions in the community forest in Karyasari Village, Leuwiliang District, Bogor Regency. Data collection is done by semi-structured interview, observation and recording of secondary data. The type of pest management carried out by the community uses three pest management techniques, including chemical, mechanical and a mixture of chemical and mechanical. Farmers do not use biological techniques. Mechanical pest management is less used in society compared to chemical management. Many farmers use chemical management techniques with pesticides because they kill pests quickly. In addition, some small farmers use a mixture of chemical and mechanical management. There is a relationship of perception with the characteristics of respondents, such as land area, education and role in society. There is a relationship of action with the characteristics of respondents, such as the role in society, land area, education and employment.